2006
DOI: 10.1037/0096-1523.32.3.558
|View full text |Cite
|
Sign up to set email alerts
|

On the relationship between the redundant signals effect and temporal order judgments: Parametric data and a new model.

Abstract: Paradigms used to study the time course of the redundant signals effect (RSE; J. O. Miller, 1986) and temporal order judgments (TOJs) share many important similarities and address related questions concerning the time course of sensory processing. The author of this article proposes and tests a new aggregate diffusion-based model to quantitatively explain both the RSE and TOJs and the relationship between them. Parametric data (13 stimulus onset asynchronies) from an experiment with pairs of visual stimuli (62… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 66 publications
(128 reference statements)
3
30
0
Order By: Relevance
“…The facilitation effects observed in the valid cue condition could have led to such increased processing speed that the second stimulus component itself could not substantially speed up the detection processes: The more efficiently a signal is processed the smaller is the expected redundancy gain. By analogy, if targets are presented at different eccentricities, redundancy gains are often reported to be smaller for targets presented at more central locations (i.e., if the target falls into the small receptive fields of the fovea) than for targets presented at more peripheral locations (Schwarz, 2006). In line with this, the pip-and-pop effect (Van der Burg et al, 2008) also has been found to be greater in invalidly cued search displays than in correctly cued ones (Zou, Müller & Shi, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The facilitation effects observed in the valid cue condition could have led to such increased processing speed that the second stimulus component itself could not substantially speed up the detection processes: The more efficiently a signal is processed the smaller is the expected redundancy gain. By analogy, if targets are presented at different eccentricities, redundancy gains are often reported to be smaller for targets presented at more central locations (i.e., if the target falls into the small receptive fields of the fovea) than for targets presented at more peripheral locations (Schwarz, 2006). In line with this, the pip-and-pop effect (Van der Burg et al, 2008) also has been found to be greater in invalidly cued search displays than in correctly cued ones (Zou, Müller & Shi, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…f f The adjusted models describe only the mean RTs (see, e.g., Schwarz, 2006), although Schwarz (1994, Appendix B) derived an explicit prediction for the variance of D for different SOAs. Using two additional parameters for the variance of M and the correlation between D and M ( 2 M , DM ), it is possible to describe the variance of the observed RTs as well.…”
Section: Methodsmentioning
confidence: 99%
“…Lateralized stimulus presentation was necessary because, in a pilot study, weak central stimuli turned out to be so salient that the mean RTs for centrally presented weak and strong visual stimuli did not significantly differ. Moreover, presenting visual and auditory stimuli left and right of central fixation allows for manipulation of the distance between the stimulus components (e.g., Gondan et al, 2005;Schwarz, 2006) in follow-up experiments. Visual stimuli were either of high intensity (V; Michelson contrast, .98) or of low intensity (v;Michelson contrast,.20).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, when subjects are not discouraged from making so-called fast guesses-that is, responses given without processing the stimulus and assumed to be much faster than regular responses-or if display conditions are such that stimuli are sometimes not detected at all, it has been shown (Eriksen, 1988;Gondan & Heckel, 2008;Miller & Lopes, 1991;Miller & Ulrich, 2003) that the power of the RMI test to detect violations of the race model diminishes. Here, we show that this holds not only for the case in which subjects are missing a proportion of the stimuli, but also when an experimenter excludes a proportion of the responses, by censoring the RT distributions from the left and/or the right-that is, excluding responses below and/or above a certain RT value because they are considered to be anticipations or outliers (e.g., Giray & Ulrich, 1993;Leo, Bertini, di Pellegrino, & Là-davas, 2008;Miller & Van Nes, 2007;Savazzi & Marzi, 2008;Schwarz, 2006). Furthermore, the experimenter may miss a proportion of the responses by not registering reactions given after some arbitrary upper bound; up to 8% of responses have sometimes been eliminated this way (see Gondan, Vorberg, & Greenlee, 2007;Miller, 2007aMiller, , 2007bMiller & Van Nes, 2007).…”
Section: Max[f X (T R ) F Y (T R )] F Xy (T R ) (6)mentioning
confidence: 99%